MANAJEMEN KESIAPSIAGAAN DALAM MENGHADAPI POTENSI BENCANA DI KABUPATEN SUMEDANG - Ida Yunari Ristiani (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2020)
Preparedness Management to face disaster Sumedang Regional Government in synergy with the TNI / Polri, Basarnas, BPBD, and Disaster Volunteers. Data from the Sumedang BPBD in 2019 approximately 326 events, the highest disasters were fires, landslides and floods. The purpose of this study was to determine community preparedness with a qualitative method with a descriptive approach. The process of collecting data is by observation, interview and documentation. The results of the study there are 4 items: organizational elements, counseling and training, disaster mitigation, risk, danger, vulnerability, ability, and 4 stages of training. A study of these four items is very useful for communities in potential disaster areas. Keywords: Management, Preparedness and Potential Disasters.